Importance of Internal Courtyards in Designing Historical and Contemporary Masjid - Salma Dwidar; Hala Sirror; Amani Derbali; Donia Abdelgawad; Amal Abdelsattar (Journal of Islamic Architecture, 2022)
The architecture of Masjids has spread in areas with harsh climates and natural conditions. In previous decades, the Masjid's design was a large flat area with an inner courtyard in the middle. This architectural design of the Masjid was appropriate to the nature of the hot climate. Recently, the design of Masjids became closed and flat areas that lack ventilation and good lighting. The research paper is based on an analytical descriptive study to determine the importance of internal courtyards in historical Masjids in Egypt and the elements that affect the significance of the courtyard in contemporary Masjids. The results show the importance of using the inner courtyard when designing a modern Masjid, which achieves many positive results, regarding the climatic and social aspects, by increasing the thermal and psychological comfort of the prayers.